Management techniques for employee engagement in contemporary organizations - Sharma, Naman, 1986-; Chaudhary, Narendra, 1983-; Singh, Vinod Kumar (Business Science Reference, 2019)
"This book identifies the various issues which affect the employee engagement and propose the various solutions to resolve the ongoing issues. It helps to unfold the various facets of the employee engagement and related aspects"--